2002
DOI: 10.1093/carcin/23.11.1919
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil increases mitochondrial phospholipid unsaturation, upregulating reactive oxygen species and apoptosis in rat colonocytes

Abstract: We have shown that a combination of fish oil (high in n-3 fatty acids) with the butyrate-producing fiber pectin, upregulates apoptosis in colon cells exposed to the carcinogen azoxymethane, protecting against colon tumor development. We now hypothesize that n-3 fatty acids prime the colonocytes such that butyrate can initiate apoptosis. To test this, 30 Sprague-Dawley rats were provided with diets differing in the fatty acid composition (corn oil, fish oil or a purified fatty acid ethyl ester diet). Intact col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 41 publications
12
93
1
1
Order By: Relevance
“…Once these factors are released from mitochondria, apoptosis is accelerated 75 . These findings were confirmed in vitro 22 as well as in vivo 51 . As mentioned above, changes in mitochondria can influence the total level/ activity of pro-and antiapoptotic proteins of the Bcl-2 family associated with these organelles.…”
Section: Dha-mediated Modulation Of Selected Apoptosis Regulatory Prosupporting
confidence: 59%
See 1 more Smart Citation
“…Once these factors are released from mitochondria, apoptosis is accelerated 75 . These findings were confirmed in vitro 22 as well as in vivo 51 . As mentioned above, changes in mitochondria can influence the total level/ activity of pro-and antiapoptotic proteins of the Bcl-2 family associated with these organelles.…”
Section: Dha-mediated Modulation Of Selected Apoptosis Regulatory Prosupporting
confidence: 59%
“…Experimental studies have shown that DHA functions as a potent suppressor of colon cancer cell proliferation in vitro 48 as well as in vivo 49 , simultaneously inducing cell death in a dose-and time-dependent manner 50 . The inhibitory effects of a fish oil diet or purified EPA or DHA on the incidence and number of colon preneoplastic loci or tumours induced by azoxymethane (AOM) or 1, 2-dimethylhydrazine in rats have been studied for a long time 51 . N-3 PUFAs, preferentially DHA, suppressed in vivo growth and induced apoptosis of human colon carcinoma xenografts in athymic nude mice 52 .…”
Section: Molecular Mechanisms Of Dha Action In Colon Cancer Cellsmentioning
confidence: 99%
“…The percentage of each fatty acid relative to total fatty acids detected in each sample was calculated and expressed as a mol%. Unsaturation index was calculated as in Eqn 1, where the mol% was multiplied by the number of double bonds in a fatty acid then summed for all fatty acids and this value was divided by 100 (Hong et al, 2002):…”
Section: Phospholipid Fatty Acid Analysismentioning
confidence: 99%
“…Mitochondria produce a considerable quantity of reactive oxygen species (ROS), including superoxide and hydrogen peroxide, which can cause damage to the macromolecules of cells (Van Houten et al, 2006). Previous studies reported that ROS production in myocardial cells is correlated with the unsaturation index of cardiolipin acyl chains (Hong et al, 2002). Of special note, the oxidation of the cardiolipin acyl chains is closely associated with the cytosolic release of cytochrome c from the mitochondria, which triggers the catalytic activation of caspase-3 (Petrosillo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%